Integration of the Kungkum Sinden Tradition in Sendang Made for the Development of a Critical Thinking E-book - Wiwik Wulandari; Aris Rudi Purnomo (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
This research focuses on developing an integrated e-book that incorporates the local wisdom of the Kungkum Sinden tradition in Sendang Made into ecosystem learning to enhance junior high school students’ critical thinking skills. The research addresses the limited availability of contextual teaching materials and the need for digital resources that support 21st-century learning, particularly critical thinking and technology integration. A Research and Development (R&D) method was employed using the ADDIE framework, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation involving science education lecturers and a science teacher, as well as readability testing. The e-book achieved high validation scores: 3.18 for presentation (valid), 3.32 for content feasibility (very valid), and 3.41 for language appropriateness (very valid), with an overall validity of 83% and a rating of very valid. The product integrates ecosystem concepts with local ecological values and interactive features designed to train interpretation, analysis, inference, evaluation, explanation, and self-regulation skills. In conclusion, the developed e-book is highly feasible and valid for supporting contextual science learning and improving students’ critical thinking skills.